Estimation of the agricultural profitability of rural enterprises in the Mixteca region of Oaxaca - Barrios Puente, Gerónimo; Rosales Hortiales, Arisbeth; Sangerman-Jarquín, Dora María; Pérez Soto, Francisco; González López, Mariano; Reyes Muro, Luis (Revista Mexicana de Ciencias Agrícolas, 2021)
In the Mixteca region of Oaxaca, rural poverty predominates, and the common economic activity is agriculture; however, the agricultural sector is precarious and has not reduced poverty. There are small plots, low value-added traditional products, old-technology techniques and there is no investment in capital. In this sense, it is necessary to know the economic benefits generated by the production units (PUs), visualizing them as rural enterprises. The objective of the research was to make an approximation to the estimation of the profitability of the agricultural production of the rural enterprises in the Mixteca region of Oaxaca for 2007 and to know what the main factors that influenced this profitability were, for this, the income and costs of the rural enterprises by municipality were estimated, their difference yielded the profitability value, and the factors that influence it were determined by means of ordinary least squares. The results indicated that profitability by rural enterprises was in the range from $-19 000 to $13 000, by municipalities from $-4 million to $4 million and by area, from $-9 000 to $6 500 per hectare. The production, improved seeds and size of PUs positively influenced the profitability value, while self-consumption, lack of infrastructure, communal property and income derived from government support decrease it. Finally, it is necessary to promote the association of producers that allows increasing production and increasing selling practices to generate greater benefits derived from agriculture.
Keywords: agriculture; production units; profits; self-consumption